Análisis de la política pública de zonas de reserva campesina : una política motivada por el campesinado, para el campesinado (2017)
"The peasant reserve zones are a tool of territorial planning created through the law 160 of 1994 of agrarian reform. This policy is created to promote the access for land to the peasants, who had lost it due to economic and violent circumstances. The policy of the peasant reserve zones was achieved thanks to an articulation of interests by the peasant organizations and that has been manifested through protests in decades. In this assignment, an analysis of the process of formulation and regulation of the peasant reserve zones policy will be made based on the multiple streams approach of John W. Kingdon, so the policy entrepreneur can be identified, and how the three streams (politics, policy, problema) align to open the policy window." -- Tomado del Formato de Documento de Grado.